+0  
 
0
388
1
avatar

(g^7)h^4*gh^5 simpilfy

Guest Jun 17, 2017

Best Answer 

 #1
avatar+17745 
+1

(g7)·h4·g·h5  =  ( g· g ) · ( h4 · h5 )  =  ( g7 + 1 ) · ( h4 + 5 )  =  ( g8 ) · ( h9 )  =  g8 · h9 

geno3141  Jun 17, 2017
 #1
avatar+17745 
+1
Best Answer

(g7)·h4·g·h5  =  ( g· g ) · ( h4 · h5 )  =  ( g7 + 1 ) · ( h4 + 5 )  =  ( g8 ) · ( h9 )  =  g8 · h9 

geno3141  Jun 17, 2017

22 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.